The Impact of Infrastructure Spending on Economic Growth: A Case Study of Indonesia - Syadullah, Makmun; Setyawan, Dhani (Communications - Scientific Letters of the University of Zilina, 2021)
This paper aims to analyze the impact of infrastructure spending on economic growth in Indonesia, which includes investment in road, port and irrigation infrastructure. The period of observation was 2011-2018, which covered 29 provinces with consideration of data availability. This study employed the growth model with a panel data analysis, which analyze the relationship between the economic growth and government investment in infrastructure in the long run. The most essential finding in this study is that the economic growth is positively influenced by government investment in road, port and irrigation infrastructure. Road infrastructure investment has a significant positive impact and the effect occurs in the fourth year after infrastructure development. In comparison, port and irrigation infrastructure investment have a positive but not significant impact to other variables.
Keywords: infrastructure investment; economic growth; transportation; public investment; agriculture